Data Set for Comparative Analysis of Blast Prediction Software for Far-Field Shock Wave Effects Behind a Blast Wall - Chester, Alastair (Cranfield University, 2024)
A comparative analysis of blast prediction software for far-field shock wave effects behind a blast wall. Performed using Autodyn, BlastFoam, ProSAir, Viper::Blast and WALAIR++. The resulting software setup file examples are included here.
A comparative analysis of blast prediction software for far-field shock wave effects behind a blast wall. Performed using Autodyn, BlastFoam, ProSAir, Viper::Blast and WALAIR++. The resulting software setup file examples are included here.
Keywords: CFD; Explosives; Blast; Blast Wall